2018
DOI: 10.1093/cid/ciy1128
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae of Congenital Cytomegalovirus Following Maternal Primary Infections Are Limited to Those Acquired in the First Trimester of Pregnancy

Abstract: Background The known relationship between the gestational age at maternal primary infection an the outcome of congenital CMV is based on small, retrospective studies conducted between 1980 and 2011. They reported that 32% and 15% of cases had sequelae following a maternal primary infection in the first and second or the third trimester, respectively. We aimed to revisit this relationship prospectively between 2011 and 2017, using accurate virological tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
125
2
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 29 publications
2
125
2
12
Order By: Relevance
“…In 4 cases the patients were infected during the first trimester, 7 during the second trimester and 1 during the third trimester, in 24 cases the period of infection was not specified. As in other congenital infections (CMV, rubella, toxoplasmosis) the risk seems greater when the infection occurs early during pregnancy, but a late trimester infection does not exclude the possibility of severe fetal consequences. We also observed that congenital herpes infection can result from a primary or a non‐primary infection, although none of the reports distinguished recurrent versus initial non‐primary infections with a different herpes simplex type.…”
Section: Discussionmentioning
confidence: 94%
“…In 4 cases the patients were infected during the first trimester, 7 during the second trimester and 1 during the third trimester, in 24 cases the period of infection was not specified. As in other congenital infections (CMV, rubella, toxoplasmosis) the risk seems greater when the infection occurs early during pregnancy, but a late trimester infection does not exclude the possibility of severe fetal consequences. We also observed that congenital herpes infection can result from a primary or a non‐primary infection, although none of the reports distinguished recurrent versus initial non‐primary infections with a different herpes simplex type.…”
Section: Discussionmentioning
confidence: 94%
“…Unlike reactivation of maternal CMV infection, or reinfection of a seropositive mother with a new strain, this type of CMV infection can be diagnosed during pregnancy. Although no country has formally recommended that all pregnancies should be routinely screened for primary CMV infection, such screening is very common in several, including Italy and France . This means that virologists in those countries have amassed extensive experience in providing precise diagnoses in real time so that individual women can make decisions about their pregnancies.…”
mentioning
confidence: 99%
“…Those who have both IgG and IgM antibodies are then tested for CMV avidity, where high avidity represents infection in the past (usually before conception) whereas low avidity often represents primary infection in the first trimester of pregnancy . It is possible to test the initially seronegative women again later in pregnancy for IgG antibodies to see if they have seroconverted, but this is less attractive because of the desire to reduce the major effects of primary CMV infection which follow infection in the first trimester …”
mentioning
confidence: 99%
“…Therefore, we think that this model should apply following maternal primary infection (MPI) before 14 weeks’. Indeed, only those fetuses are at risk of long‐term sequelae with a 32.4% risk of sensorineural hearing loss and/or neurologic sequelae . Pregnant women infected after 14 weeks’ gestation should be reassured and prenatal surveillance should not be heightened.…”
mentioning
confidence: 99%
“…We aimed to evaluate the predictive value of the addition of MRI to prenatal ultrasound and found that the combination of both normal second‐trimester ultrasound and third‐trimester MRI had a 100% negative predictive value on the development of sequelae . This is extremely valuable information at 32 weeks’ gestation for a condition bearing an overall risk of sequelae of 32% . In addition, we agree that access to fetal MRI is limited in many countries and that is why we also assessed the value of third‐trimester ultrasound alone. Barra et al also question third‐trimester investigations because there is no prenatal therapy available.…”
mentioning
confidence: 99%